CONTEXTUALIZATION OF SCIENTIFIC AND RELIGIOUS VALUES IN MULTICULTURAL SOCIETY - Dalmeri, Dalmeri (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2015)
This paper is the result of research applying reflective philosophical approach that try to answer the the question about the integration of the values of science and the values of the Islamic religion to shape the character of college students and the contextualization of religious values in the development science and technology in the multicultural era such as Indonesia. The findings of this research is, that Islam as a religion has always advocated Muslims to always holds integration, because, religion and science are not contradictive. and controversial, but complementary. Such a perspective, factually was able to build positive character among students in Jakarta, because for them religion is seen as a driving force for the development of science and discovery in science and technology should be aligned with the values of Islam, so it is not pulled out from the roots of religious values sublime.***Tulisan hasil riset dengan pendekatan penelitian reflektif filosofis terhadap integrasi nilai-nilai sains dan nilai-nilai agama Islam ini, mencoba menjawab persoalan integrasi nilai-nilai sains dan nilai-nilai agama Islam untuk membentuk karakter mahasiswa perguruan tinggi dan kontekstulisasi nilai-nilai agama dalam perkembangan sains dan teknologi di era multikultural seperti Indonesia. Adapun temuan peneletian ini adalah, bahwa Islam sebagai sebuah agama selalu menganjurkan umatnya untuk selalu berpandangan integratif. Sebab, antara agama dan sains tidak bersifat kontradiktif dan berlawanan, melainkan saling melengkapi. Cara pandang seperti ini, ternyata mampu membentuk karakter positif di kalangan mahasiswa perguruan tinggi di Jakarta, sebab bagi mereka agama dipandang sebagai pendorong bagi perkembangan ilmu pengetahuan dan penemuan sains dan teknologi harus diselaraskan dengan nilai-nilai Islam, sehingga tidak tercerabut dari akar nilai-nilai agama yang luhur.